Web Based Supervisor Supervisee Project Matching System - Messaoud, Benotmane (2010)
This study aims to develop a web-based supervisor-supervisee matching system to automatically match relevant research area topics and lecturers with students' knowledge and skills. The web-based supervisor-supervisee matching system is often used in educational organizations due to its effectiveness in facilitating and enhancing the monitoring of the supervision of project papers. To develop such system, there has been a combination of both the general methodology on one hand, and Nunamaker's system research process approach lo develop the system, on the other hand. The data used in this study was drawn from time tables and students' achievement records provided by the UUM IT faculty. Finally, data analysis was done following the development of the system which was based on the matching algorithm suggested in this paper. The algorithm was found to be good as it proved to have an accuracy of 81.39%, suggesting the efficiency and feasibility of the system.